Les pêches méditerranéennes - Boude, Jean-Pierre (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1987)
The Mediterranean together with the Black Sea constitutes a fishing ground of almost 3 000 000 square kilometres. In view of its geographical location, numerous conflicts arise in this area regarding its exploitation since 22 states have direct access to its waters. Total fish catch in the Mediterranean amount to almost 1 900 000 tons per year with a rise of 136 % over 20 years. This industry employs nearly 250 000 fishermen. The occupations vary greatly in general and the exploitable resources are shared inequitably. The state of exploitation is such that the financial returns are extremely uneven, hence the requisite for profitability sometimes leaves much to be desired. Although potential development of stock appears limited, changes in reception facilities, production instruments, planning of coastal and lagoon areas, and better training of fishermen would improve the situation in this industry. The setting-up of Mediterranean integrated programmes can be a step forward towards the realization of this goal.